Research progress on eco-product value realization and rural revitalization and its inspiration for karst desertification control: a systematic literature review between 1997 and 2023 - Yan, Jiawang; Xiong, Kangning; Fu, Yue; Yu, Nana; Zhang, Zefu; Zheng, Peng (Frontiers in Sustainable Food Systems, 2024)
Ecological product value realization (EPVR) and rural revitalization (RR) are essential guarantees for ensuring human well-being and a better life. They are also crucial components of a promising vision for the future of the world and play a significant role in promoting the sustainable management of ecological restoration. The chain-driven mechanism of EPVRecological industry (EI) -RR in the karst desertification control (KDC) area has already become a key scientific issue that urgently needs to be solved during the process of promoting industrial green transformation and consolidating the results of poverty alleviation in the region, however, there is currently no clear synthesis of this issue. To address this shortfall, we have adopted a systematic literature review (SLR) framework. Based on the Web of Science (WOS) and the China National Knowledge Infrastructure (CNKI) databases, we conducted a comprehensive literature search and rigorous evaluation, obtaining 321 documents published between 1997 and 2023. These documents were systematically integrated and analyzed in depth through a systematic literature review process, aiming to provide a holistic perspective. The results indicate that (1) there is an overall fluctuating upward trend in the number of literatures issued in the time series, and the study trend is categorized into accumulation, development, and expansion periods; (2) the research area is mainly concentrated in China's EPVR and RR pilot areas. There is a significant overlap between the hotspot of research institutions, their areas of specialization, research foundations, and geographical locations. The research content mainly includes EPVR, EI, relationship between EI and RR, models of RR and EPVR pathways; (3) the main progress and landmark results are summarized based on the research content. A series of related scientific issues and technical needs, such as eco-product (EP) value accounting, value realization mechanisms, EI formation, RR, and the chain-driven mechanism between them, are explored for future research. While summarizing the general laws, it also provides targeted insights and revelations for the subsequent sustainable management of the KDC ecosystem.